PENATALAKSANAAN FISIOTERAPI PADA KONDISI DELAY DEVELOPMENT (DD) DENGAN MODALITAS NEURO SENSO MOTOR REFLEK DEVELOPMENT AND SYNCHRONIZATION (NSMRD & S) DAN MASSAGE ORAL DI YPAC SURAKARTA - Fany Anggraeni; Nur Susanti (LPPM Universitas Pekalongan, 2021)
Delay Development is a delay in two areas/more development of rough motors, smooth motors, languages, personal/social and daily activities. Problematics delay development is decreased growth of flowers, sensory disorders, reflec disorders, muscular strength disorders and decreased functional ability. Physiotherapy examination includes the growth of DDST with Blanko, sensory with sensory Blanko, Reflec with Blanko Reflec, muscle strength with XOTR and functional ability with Blanko GMFM. Its intervention technology is NSMRD & S and Oral Massage. Research aims to determine the influence of physiotherapy management in the condition of delay development with the modalities NSMRD & S and Massage Oral. Research was conducted at YPAC Surakarta with the design of analytical descriptive research. His research draft is case study draft. Research subjects are patients with delay development modalities of NSMRD & S and Oral Massage. The method of collecting data in this study uses the Heteroanamnesis method. Research instruments in the form of DDST, Blanko Sensoris, Blanko Reflek, XOTR, and GMFM. The results of the study 6 times the following therapy: (1) Increased growth of flowers, (2) improvement of the vestibular sensory enhancement, (3) child reflecs found at age 7-9 months, (4) Increased muscle strength, (5) No increase in functional ability. Because of the research that the modalities of NSMRD & S and Oral Massage can reduce problems in the condition of delay development.